Особливості параметрів самосвідомості працівників ОВС з різним рівнем конфліктності - Гіренко, С. П.; Girenko, S. P.; Сергій Гіренко (Вісник Національного університету оборони України. - 2014. - Вип. 5. - С. 30-35, 2014)
В статті розглянуто низку параметрів самосвідомості працівників ОВС, які мають різний рівень особистісної конфліктності. Окреслено зміст понять та особливості самооцінки, рівня домагань та значущості основних сфер життя працівників ОВС.

The article describes a number of parameters self-consciousness of law enforcement officers to have a different level of personal conflict. Determine the content of the concepts and features of selfesteem, level of aspiration, and the significance of the main spheres of life of employees of police officers. The author examines the conflict as a special form of individual values clash motivation,behavioral change mechanism status of the individual in society. The article is an analysis of scientific papers on the problem of conflict and self-identity. The basic function and structure of psychological conflict consciousness - self-conflict and conflict self-esteem. The results of self-diagnosis, level of aspiration and performance significance of various walks of life police officers with different levels of conflict.

В статье рассмотрен ряд параметров самосознания личности сотрудников ОВД с имеющими различный уровень личностной конфликтности. Определены содержание понятий и особенности самооценки, уровня притязаний и значимости основных сфер жизни работников ОВД.
Особенности параметров самосознания работников ОВД с различным уровнем конфликтности
Features parameters of consciousness policemen with different levels of conflict
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; Юридична психологія. Legal psychology. Юридическая психология; конфлікт; правоохоронна діяльність; самооцінка; самосвідомість; сфери життя; ціннісні орієнтації; conflict; law enforcement activity; self-esteem; self-awareness; spheres of life; value orientations; конфликт; правоохранительная деятельность; самооценка; самосознание; сферы жизни; ценностные ориентации